2015
DOI: 10.1037/a0038861
|View full text |Cite
|
Sign up to set email alerts
|

Modeling naturalistic craving, withdrawal, and affect during early nicotine abstinence: A pilot ecological momentary assessment study.

Abstract: Despite the critical role of withdrawal, craving, and positive (PA) and negative affect (NA) in smoking relapse, relatively little is known about the temporal and predictive relationship between these constructs within the first day of abstinence. This pilot study aims to characterize dynamic changes in withdrawal, craving and affect over the course of early abstinence using ecological momentary assessment. Beginning immediately after smoking, moderate and heavy smoking participants (n = 15 per group) responde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 69 publications
1
29
0
Order By: Relevance
“…To our knowledge, this study is the first to use EMA to examine the relationship between low positive affect and craving in PODPs. The finding that low daily levels of positive affect are associated with greater same day cravings, but only for individuals with lower general levels of positive affect, provides a nuanced extension of findings from several studies that have used questionnaire measures of low positive affect in alcohol-dependent outpatients (McHugh et al, 2012), as well as EMA studies of nicotine-dependent patients (Bujarski, et al, 2015; Cook et al, 2004; Dunbar et al, 2010; Shiffman et al, 2014; Shiffman & Paty, 2006; Versace et al, 2011); although reports have been mixed in studies of nicotine-dependence (Shiffman et al, 2002; Shiffman & Waters, 2004). …”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…To our knowledge, this study is the first to use EMA to examine the relationship between low positive affect and craving in PODPs. The finding that low daily levels of positive affect are associated with greater same day cravings, but only for individuals with lower general levels of positive affect, provides a nuanced extension of findings from several studies that have used questionnaire measures of low positive affect in alcohol-dependent outpatients (McHugh et al, 2012), as well as EMA studies of nicotine-dependent patients (Bujarski, et al, 2015; Cook et al, 2004; Dunbar et al, 2010; Shiffman et al, 2014; Shiffman & Paty, 2006; Versace et al, 2011); although reports have been mixed in studies of nicotine-dependence (Shiffman et al, 2002; Shiffman & Waters, 2004). …”
Section: Discussionmentioning
confidence: 54%
“…Short term increases in PA have also been associated with a decreased risk for smoking lapse, suggesting PA may play a protective role in early nicotine abstinence (Ferguson, Shiffman, & Gwaltney, 2006). Bujarski et al (2015) also found that PA was negatively correlated with craving, whereas the level of withdrawal/NA was positively associated with craving. However, the temporal dynamics were different, demonstrating the independent role of PA in nicotine abstinence over and above that of NA.…”
Section: 0 Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Participants then underwent the mood induction while smoking an experimental cigarette (either NIC+ or NIC−) or holding a pen (minute 0 on Figure 1b timeline: 27 minutes after finishing own-brand cigarette). We designed the experiment so that the latency between own-brand smoking at the beginning of each trial and the smoking manipulation would be less than 30 minutes, a time period too brief to produce, on average, significant increases in withdrawal symptoms (Bujarski et al, 2015; Hendricks, Ditre, Drobes, & Brandon, 2006). Mood was assessed immediately after mood induction (Time 1), and then again at 7 minutes (Time 2, immediately after smoking NIC+, NIC− or holding a pen) and at 18 minutes after the start of mood induction (Time 3: see Figure 1b).…”
Section: Methodsmentioning
confidence: 99%
“…Low PA has been associated with greater craving (Huhn et al, 2016; McHugh et al, 2013), and high levels of PA have been associated with both higher and lower levels of craving in the laboratory (Mason et al, 2008; Maude-Griffin & Tiffany, 1996; Schlauch et al, 2013; Tiffany & Drobes, 1990) and in the EMA (Bujarski et al, 2015; Epstein & Preston, 2010) literature. Emotional states that produce high PA might place individuals in a celebratory mood, encouraging drug use for hedonic reasons (Baker, Morse, & Sherman, 1987; Robinson & Berridge, 1993).…”
Section: Introductionmentioning
confidence: 99%